Increasing the Income of SMEs in Indonesia through the Power of Quality and Education: Meningkatkan Pendapatan UKM di Indonesia melalui Kekuatan Kualitas dan Pendidikan - Farhansyah, Rizky Fajar; Sriyono (Indonesian Journal of Law and Economics Review, 2024)
This study explores the impact of product quality and the educational level of small and medium enterprise (SME) owners on SME income in Sidoarjo Regency, Indonesia. Using a quantitative approach with survey data from 52 SMEs, the analysis via SMARTPLS4 reveals that both product quality and education significantly influence SME income. The findings suggest that enhancing product quality and investing in education can lead to higher SME income, providing valuable insights for SME owners and policymakers to support economic growth in the region. Highlight: Impact: Product quality and education level significantly influence SME income. Method: Analyzed 52 SMEs in Sidoarjo using SMARTPLS4. Recommendation: Improve product quality and education to boost SME income. Keyword: SMEs, product quality, education level, income, Sidoarjo Regency